The Development of the Royal Botanic Garden Edinburgh ‘Certificate in Practical Horticulture’ - Morris, Leigh; Cohen, Laura (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2010)
The Royal Botanic Garden Edinburgh (RBGE) has a long history of delivering high-quality practical horticultural training within the UK and abroad. In 2007 this training was formalised by the RBGE Education Department into the ‘RBGE Certificate in Practical Horticulture’ (CPH) programme. The vision for the CPH was to create an internationally recognised and standardised, yet flexible and practical horticultural qualification, predominantly, but not exclusively, for the botanic gardens sector. Providing a measurable educational outcome for international development projects is increasing the contribution that RBGE makes to target 15 of the Global Strategy for Plant Conservation. This paper reviews the development of the CPH programme, through its initial conception, the writing of the first course syllabus, the evolution of the course structure and content, up to the course now being offered today. The initial success of the CPH is discussed, detailing the different locations in which the course has been delivered to date and the other gardens that are now offering the CPH themselves. Recent developments are discussed, including the endorsement of the course by Botanic Gardens Conservation International (BGCI) and the funding awarded by the Stanley Smith (UK) Horticultural Trust in 2010 for course development. The paper ends by highlighting the future objectives for the CPH, including the development of new and improved tutor and learner support materials, the offering of ‘train the trainer’ programmes that will facilitate the wider uptake of these courses and the vision for the programme to become a benchmark for practical horticultural training worldwide.